The Concept of Water Rights in ISlam and Water Resource Stress in the Middle East: Economic Implications for International Security - Al-Roubale, Amer; Vicas, Alex (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Concept of Water Rights in ISlam and Water Resource Stress in the Middle East: Economic Implications for International Security